Transforming Islamic Finance: Innovation Opportunities, Global Challenges, and the Role of Artificial Intelligence in Islamic Financial Management - Emelda Sari (Athallah Publishing Globalindo, 2025)
Islamic finance is undergoing a major transformation in the digital age, driven by technological advancements such as artificial intelligence (AI), blockchain, and fintech. This research highlights the opportunities and challenges of digitalization in maintaining compliance with Shariah principles in the financial sector. Using a descriptive qualitative approach through a literature review, data was collected from international journals, industry reports, and regulatory documents. Thematic analysis was conducted to identify key themes, namely technological innovation, regulatory challenges, and Shariah compliance. The results show that AI and blockchain are important in improving operational efficiency and financial inclusion in the Islamic finance sector. AI supports fast data processing and personalization of services, while blockchain provides transparency and security of transactions. This technology expands access to Islamic finance to remote areas. However, key challenges include the digital divide, regulations that are not yet responsive to technological developments, and the need for strict supervision to maintain compliance with Shariah principles. The study concludes that digitalization offers great potential to advance Islamic finance. However, its success requires collaboration between financial institutions, regulators, and technology developers. Strategic efforts to address the challenges of regulation, data security, and technology accessibility are essential for such innovations to be sustainable and in line with Shariah values.